GAMBARAN KONTAMINASI Salmonella spp PADA BOTOL SUSU DAN KEJADIAN DIARE BAYI DAN BALITA (Studi di Kelurahan Tandang Kecamatan Tembalang) - Devi Priyantika; Martini Martini; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Diarrhea is still a world health problem, especially in developing countries. The highest number of cases at the Village level in Central Java is in Tandang. Consumption of infant formula as one of breastfeeding substitutes in infants use is increasing. Researchers are interested in doing this research because there are still many cases of diarrhea due to Salmonella spp infection that can lead to more severe cases of diarrhea or to cause outbreaks in the future. The purpose of this research was to describe Salmonella spp contamination in milk bottles with the incidence of infant and toddler diarrhea. The research design was cross-sectional analytic. The sampling technique by purposive random sampling was 97 respondents. The result shows that the highest percentage by age of Salmonella spp contamination at age 12-<24 months, whereas the incidence of diarrhea at age 0- <6 months.The highest percentage of caregiver knowledge of Salmonella spp contamination and diarrhea in the respondents who well categorized.The highest percentage of Salmonella spp contamination and the incidence of diarrhea in bad bottle sanitation variables. Source of water in the manufacture of milk derived from gallons has the highest percentage of Salmonella spp contamination, while the highest presentation on diarrhea occurrence is in good water. The health workers suggested of increasing personal hygiene and sanitation to the mother/caregiver